2021
DOI: 10.1002/leg3.83
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric heating‐assisted disinfestation of black gram and its effect on protein profile: A comparative study on radio frequency and microwave heating

Abstract: Pulse beetle, Callosobruchus maculatus, is the major pest infesting in the stored legumes. The present study is aimed to evaluate the comparative efficacy of radio frequency (RF) and microwave (MW) heating treatments to eradicate the problem of infestation at all four life stages in blackgram (Vigna mungo). Infested blackgram kernels in a single egg, larvae, pupae, and adult stage were subjected to RF and MW irradiation at 180-, 190-, 200-, and 210-mm electrode heights for RF and at 365, 295, 250, and 230 W MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…(2021) and Tiwari et al. (2021). The endothermic peak obtained at 380°C (D) in FD BSFP and SD BSFP flour at 480°C (D) revealed the degradation of chitin components.…”
Section: Resultsmentioning
confidence: 97%
“…(2021) and Tiwari et al. (2021). The endothermic peak obtained at 380°C (D) in FD BSFP and SD BSFP flour at 480°C (D) revealed the degradation of chitin components.…”
Section: Resultsmentioning
confidence: 97%
“…But the study by Vadivambal et al (2008) in barley damaged by T. castaneum revealed that eggs are more susceptible and adults are least susceptible to microwave radiation. The studies conducted on Callosobruchus maculatus revealed that eggs were the most vulnerable and pupae were the least susceptible stage to irradiation (Shoughy and Elzun, 2014;Tiwari et al, 2021). In the case of lepidopteran storage pest, fig moth Ephestia cautella also, eggs were the most susceptible stage followed by female pupae, larvae and male pupae (Khalaf et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, RF heating achieved overall mortality in just 5.64, 6.28, and 5.35 min for all C. maculatus life stages, with insect eggs experiencing the shortest lethal time of 3.62 min ( Table 8 ). These findings highlight the rapid and effective nature of both microwave and RF radiation in controlling C. maculatus [ 90 ].
Fig.
…”
Section: Dielectric Heating For Insect Controlmentioning
confidence: 99%
“…However, this approach has significant drawbacks, including adverse effects on nontarget species, negative impacts on the preservation of the ecosystem and the evolution of resistance in pests [ 87 , 89 ]. Dielectric heating is employed to address the issue of this pest infestation in black gram beans [ 90 ]. The treatment involves using a 10 kW RF system operating at 40.68 MHz, which consists of a generator linked to an applicator designed to deliver precise and controlled RF energy to the samples.…”
Section: Dielectric Heating For Insect Controlmentioning
confidence: 99%
See 1 more Smart Citation